Potensi Kebangkrutan Suatu Perusahaan Akibat Mismanajemen - Friska Lerinsa (Universitas Nusantara PGRI Kediri, 2021)
Every single company will experience several phases of company (organization) development, better known as organizational life cycle. Organizational life cycle describes the state of an organization starting from the establishment, growth, development, to performance decline and bankruptcy. Therefore, a company needs to be able to maintain its performance so it can compete and survive when entering the organizational maturity phase, so that it will not experience bankruptcy caused by mismanagement. Bankruptcy means the failure of a company to operate, so the operational cost do not match the company’s income which will cause the company fail to pay any of its obligations. This study found that some of many causes of the bankruptcy of a company are financial distress and economic distress, both refer to one problem : failure in financial management. The methodology used in this study was qualitative method. Author conducted a literature study by collection data from several sources such as articles and research journals. The data are then processed and studied to get a conclusion about factors in a company that can lead to a bankruptcy, especially those related to management system.